The legal regulation of arbitration in Kosovo, with special emphasis on the insurance policy - Qehaja, Rustem (Array, 2018)
The subject around which this study is conducted relates to arbitration, as a method or alternative way of resolving disputes from the insurance policy. The topic discussed in this paper is of particular importance because industry respectively insurance activity represents a rather delicate activity, which wakes up considerably the interest of citizens, because through insurance they secure the most basic goods such as life, wealth, and so on. During the course of this study, I have focused on the provisions of various laws covering the insurance sector such as the Law no. 04/L-077 on Obligations, Law no. 05/L-045 on Insurance, etc., as well as in the legislation, which covers the field of arbitration, respectively in the Law no. 02/L-75 on Arbitration of the Republic of Kosovo. The settlement of disputes by the insurance policy between the parties through arbitration, gives this subject a specific character, because the use of arbitration in this field, is not studied and analyzed as much as is necessary. The purpose of this paper is to provide the reader with general knowledge on arbitration as an alternative way of resolving disputes between the parties to the insurance.